Electronic Resources Provided by Egyptian Libraries - Stewart, Kristine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This survey was focused on determining how access to electronic resources is provided by Egyptian libraries, what type of information is available electronically, and how this electronic access is supported. The geographic representation of respondents and non-respondents is presented and issues regarding electronic access in Egypt are discussed. Ce sondage a pour objectif de déterminer comment les bibliothèques égyptiennes donnent accès aux ressources électroniques, quel type d’information est disponible de façon électronique et comment est appuyé l’accès à ces ressources. Nous discuterons de la représentation géographique des répondants et des non-répondants et de l’accès aux ressources électroniques en Égypte.